Actigraphy-derived rest--activity rhythms are associated with nocturnal blood pressure in young women. Issue 12 (13th December 2021) - Hoopes, Elissa K.; Patterson, Freda; Berube, Felicia R.; D'Agata, Michele N.; Brewer, Benjamin; Malone, Susan K.; Farquhar, William B.; Witman, Melissa A.
Abstract : Supplemental Digital Content is available in the text Abstract : Introduction: Misalignment between lifestyle behaviors and endogenous circadian rhythms is associated with elevated nocturnal blood pressure (BP) in experimental studies; however, less is known about free-living (i.e. nonlaboratory) circadian disruption and nocturnal BP. Additionally, sex-specific cardiovascular implications of circadian disruption are unclear. Objective: To examine the associations between rest--activity rhythms (RAR), a field-based estimate of circadian disruption, and nocturnal BP characteristics in young men and women. Methods: Fifty participants (20 ± 1 years; 20 men/30 women) underwent 24-h ambulatory BP monitoring following 14 days of wrist actigraphy. RAR variables of interdaily stability (day-to-day consistency in RAR), intradaily variability (within-day fragmentation of RAR), and relative amplitude (difference between peak vs. trough activity) were derived from actigraphy. Multivariable regression models of mean nocturnal SBP, DBP, and SBP dipping were generated to test main associations with RAR variables, and sex × RAR interactions. Daytime BP, race, BMI, physical activity, sleep duration, alcohol, caffeine, and sodium intake were considered as covariates. Results: In the full sample, no main associations between RAR and nocturnal BP characteristics were found. Sex interacted with RAR such that in women, higher interdaily stability ( β  = −5.39, 95% CI = −10.04 to −0.73, P  = 0.024) and relative amplitude ( β  = −4.78, 95% CI = −9.22 to −0.34, P  = 0.036) were both associated with lower nocturnal SBP. Sex-stratified multivariable models of nocturnal BP also revealed associations between interdaily stability and relative amplitude with SBP dipping in women (all P  ≤ 0.01). No associations were apparent in men. Conclusion: Consistent and high-amplitude RAR are favorably associated with nocturnal BP characteristics in young women.